Biaxial stretch-induced crystallization of poly(ethylene terephthalate) above glass transition temperature: The necessary of chain mobility. (28th September 2016) - Zhang, Qianlei; Zhang, Rui; Meng, Lingpu; Lin, Yuanfei; Chen, Xiaowei; Li, Xueyu; Zhang, Wenhua; Li, Liangbin
Abstract: Strain-induced crystallization (SIC) of poly(ethylene terephthalate) (PET) slightly above glass transition temperature ( T g ) is investigated by adopting a sequential biaxial stretching mode in this work. Small angle X-ray scattering (SAXS) and wide angle X-ray diffraction (WAXD) are employed to study variation of orientation parameter and crystallinity of stretch films in machine and transverse draw ratio space. Our results reveal that improving chain mobility by stretching is necessary before crystallization occurs slightly above T g, during which the total external work of sequential biaxial stretching is not dissipated but "stored" in polymer chains with high mobility. The total crystallinity is precisely correlated with the total external work, which does not relate to stretch direction and demonstrate that enhanced chain mobility have no directionality. Considering the structures that restrict the polymer chains in the initial sample, a molecular model is proposed to interpret the structure changes during SIC of PET above T g . Graphical abstract: Highlights: A sequential biaxial stretching mode is adopted to investigate SIC of PET above T g . A molecular model is proposed to interpret structure changes during SIC of PET. Improving chain mobility is necessary before SIC occurs slightly above T g . The enhanced chain mobility by stretching has no directionality. The external work is the mainly driven force in SIC of PET slightly above T g .